Magmatism and Cu–Au–Mo mineralization of the Darbut tectono‐magmatic zone in West Junggar (Xinjiang), NW China: An updated review. (24th March 2018) - Duan, Fenghao; Li, Yongjun; Zhi, Qian; Yang, Gaoxue; Lai, Chun‐Kit; Xiao, Hong; Lindagato, Philemon; Wan, Yu; Ren, Yi
Abstract : The Darbut tectono‐magmatic zone in the West Junggar terrane (NW China) is an important component of the famous Circum‐Balkhash‐West Junggar metallogenic province. In this region, the discovery of some small but high‐quality Cu–Au deposits/prospects indicate substantial exploration potential for large porphyry Cu–Au deposits, for example, those in the neighbouring Kazakhstan. In this contribution, we concluded that the Dulunhe granite and small ore‐bearing granitoids in Baogutu are adakitic petrogenesis, and the Buerkesitai and Tasikuola granites (formed by magma mixing) are well comparable with the Xiaerpu granite. In summary, granitoids with similar petrogenesis and mineralization are distributed on both sides of the Darbut fault zone and show good correlations with the sinistral movement of the latter. We propose that the porphyry Cu–Mo–Au mineralization potential of the small calc‐alkaline I‐type granitic stocks in southern West Junggar region is significantly higher than that of alkaline A‐type large granitic batholiths. Besides, the magma mixing‐derived and adakitic granites have great prospecting potentialities. We argue that the Cu–Mo–Au mineralization in the Darbut tectono‐magmatic zone was originally E‐W trending, and then displaced by the Darbut sinistral strike‐slip faulting, instead of being controlled by NE‐NNE trending faults. The main regional mineralization pattern comprises a northern magmatic‐hydrothermal Au belt ( 318 Ma), a middle porphyry Mo belt ( 296 Ma), and a southern adakite and magma mixing granite‐related Cu–Au belt ( 313 Ma). We infer that the Bieluagaxi Au belt may continue eastward to east of Sartohay.